Агрокліматичні ресурси Волинської області в умовах сучасного клімату - Тарасюк, Ніна; Федас, Тетяна; Tarasyuk, Nina; Fedas, Tatyana (My University, 2017)
В умовах сучасного клімату на території Волинської області спостерігаємо підвищення середньорічної температури повітря, що призводить до зміни агрокліматичних показників, які є важливою передумовою розвитку рослинництва, садівництва й лісового господарства. Тому в статті проаналізовано зміни агрокліматичних характеристик за період інструментальних спостережень по території Волинської області, наведено інформацію щодо сучасних кліматичних змін. Основну увагу приділено зміні режиму температури повітря на території Волинської області, визначено відхилення показників суми позитивних середніх добових температур повітря вище від указаних меж (0, 5, 10, 15*С) та суми ефективних температур впродовж періоду спостережень з середини ХХ – початку ХХІ ст., за даними спостережень на шести метеостанціях, виокремлено періоди з дуже високою температурою повітря, установлено відхилення в тривалості вегетаційного періоду. In conditions of the modern climate on the territory of the Volyn region there is an increase in the average annual temperature of air. This leads to a change in agroclimatic indicators, which are an important prerequisite for the development of plant growing, horticulture and forestry. The changes in agroclimatic characteristics during the period of instrumental observations in the Volyn region are analyzed and information on current climate change is provided. The main attention is paid to changing the regime of air temperature on the territory of the Volyn region. Also, the deviation of the values of the sums of positive average daily air temperatures above the specified limits (0, 5, 10, 15о С) and the sums of effective temperatures during the observation period from the middle of the XX – the beginning of the XXI century is determined. According to observations at six meteorological stations, the periods with very high air temperature are highlighted and deviations in the duration of the vegetation period are established.
Agroclimatic Resourses of Volyn Region in the Conditions of the Modern Climate
Keywords: сучасний клімат; глобальні й регіональні зміни клімату; температурний режим; агрокліматичні ресурси; сума позитивних температур; вегетаційний період; modern climate; global and regional climate change; temperature mode; agroclimatic resources; sum of positive temperatures (SPT).; vegetation period